HISTOPATHOLOGICAL STUDY OF SALIVARY GLAND LESIONS IN A TERTIARY CARE HOSPITAL OF LAHORE (The Research of Medical Science Review, 2025)
Background: Some salivary gland lesions, however, are very rare neoplastic tumors; one example includes pleomorphic adenoma and mucoepidermoid carcinoma, along with some non- neoplastic conditions like chronic sialadenitis and mucoceles. Such lesions mostly simulate each other, so precise diagnosis is of great importance. Objective: To assess the frequency and distribution of various histopathological types of salivary gland lesions in patients at a tertiary care hospital in Lahore, Pakistan. Methods: A cross-sectional study was conducted at Sir Ganga Ram Hospital, Lahore, from June to December 2024. A total of 136 biopsy specimens from patients diagnosed with salivary gland lesions through Fine Needle Aspiration Cytology (FNAC) were included. The specimens were processed and evaluated histopathologically for lesion type and other relevant characteristics. Data were analyzed using SPSS version 26.0. Results: Pleomorphic adenomas were the most common lesion (39.7%), then mucoceles (19.1%), chronic sialadenitis (17.6%), and Warthin’s tumors (6.6%). The majority of lesions were located in the parotid gland (56.6%), with a significant association between lesion type and location (p <0.001). No significant differences were observed based on gender, age, or residence (p > 0.05).Conclusion: The pleomorphic adenoma is the most common salivary gland lesion, especially of the parotid gland. The histopathological examination helps differentiate between neoplastic and non-neoplastic lesions, hence proper diagnosis and management. These findings will guide clinicians in early detection and treatment to improve patient outcomes in the region.